2008
DOI: 10.1002/adsc.200800517
|View full text |Cite
|
Sign up to set email alerts
|

Ligand‐Free Iron/Copper Cocatalyzed Alkynylation Coupling Reactions

Abstract: Ligand-free iron/copper cocatalyzed cross-coupling reactions of aryl halides with terminal alkynes were carried out to provide the corresponding coupling products in good yields (up to 99%). Noteworthy is that this low-cost, effective and environmentally friendly protocol was the first to be employed in alkynylation couplings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
43
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 81 publications
(44 citation statements)
references
References 74 publications
1
43
0
Order By: Relevance
“…[13] Meanwhile, we and other groups have demonstrated efficient Fe/Cu cocatalyzed alkynylations of aryl halides. [14] Differently, Wang has disclosed that the Sonogashria coupling was investigated in the presence of ultrafine nickel powder together with CuI and PPh 3 . [14] Based on our interest on coupling reactions using easily available catalysts, [12i,j,14a,15] herein, we describe our recent finding that samarium powder could directly catalyze the alkynylation of aryl halides without using any ligands and co-catalysts.…”
mentioning
confidence: 99%
“…[13] Meanwhile, we and other groups have demonstrated efficient Fe/Cu cocatalyzed alkynylations of aryl halides. [14] Differently, Wang has disclosed that the Sonogashria coupling was investigated in the presence of ultrafine nickel powder together with CuI and PPh 3 . [14] Based on our interest on coupling reactions using easily available catalysts, [12i,j,14a,15] herein, we describe our recent finding that samarium powder could directly catalyze the alkynylation of aryl halides without using any ligands and co-catalysts.…”
mentioning
confidence: 99%
“…[11] Here, we wanted to apply these known catalytic systems to the decarboxylative coupling of 4-iodoanisole and phenylpropiolic acid as a model reaction. The results are listed in Table 1.…”
mentioning
confidence: 99%
“…Dewei Ma and co-workers reported that the N,N-dimethyl glycine promoted Ullmann coupling reaction of phenols with aryl halides at 90 o C [41]. Recently, few studies have focused on the use of copper [42][43][44], zinc [45], nickel [46], copper/iron [47] and iron [48], based catalytic systems for the synthesis of biaryl ethers by using the cross-coupling of aryl halide and phenol. However, these aforementioned protocols have one (or) more drawbacks such as use of various well designed ligands, lack of recyclability, high cost of ligands etc.…”
Section: Introductionmentioning
confidence: 99%